DEMOGRAPHIC SOCIO-ECONOMIC CHARACTERISTICS OF WOMEN AND CONTRACEPTIVE USE IN PAKISTAN - MUHAMMAD IMRAN; JAMAL ABDUL NASIR; SYED ARIF AHMED ZAIDI (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To explore the trend of different contraceptive methods at different reproductive age groups for ever married women as well as highlighting the demographic and socioeconomic characteristics that signiﬁcantly inﬂuence in the selection of contraception. METHODS: Three consecutive Pakistan demographic health survey (PDHS) surveys 1990-91, 2006-07 and 2012-03 data sets have been used for descriptive and PDHS 2012-03 for multinomial logistic regression analysis. RESULTS: Under descriptive analysis, a decline in non-user, traditional and folkloric contraceptive methods while 26.58% increment in modern contraception in PDHS 2012-13 as compared to PDHS 2006-07. The factors signiﬁcantly affecting in contraception choice by incorporating the multinomial logistic regression are as the level of female education increased the traditional and modern contraceptive use also increased, being the urban 37% more likely to use modern contraceptive methods, while Sindh and Baluchistan have less likely to use modern contraceptive as compared to Punjab, the family with no child not use any method. A positive association between wealth index and contraception, having no access to radio, television and newspaper made the respondent about 39% less likely to select the modern contraceptive methods and not visited by family planning worker in last 12 months minimized the likelihood to use contraceptive methods. CONCLUSION: Women education, location and geographical area of residence, wealth index, media access, visited by family planning worker, number of living children, desire for more children are the factors that signiﬁcantly inﬂuence the contraceptive use. While the level of modern contraception has raised in 2012-13 as compared to 1990-91 and 2006-07 in Pakistan.